A Preliminary Study on the Functional Benefits of Computerized Working Memory Training in Children With Pediatric Bipolar Disorder and Attention Deficit Hyperactivity Disorder - Passarotti, Alessandra M.; Balaban, Livia; Colman, Liza D.; Katz, Lindsay A.; Trivedi, Nidhi; Liu, Li; Langenecker, Scott A. (Frontiers in Psychology, 2020)
Twenty-nine pediatric patients (age range: 10-16 years) with working memory (WM) deficits, including children with pediatric bipolar disorder (PBD) and children with attention-deficit hyperactivity disorder (ADHD), underwent a Cogmed WM training program. For both patient groups, WM performance on Cogmed tasks and on the digit Span Test improved significantly after training. Moreover, the PBD group improved on Trails Making Test (TMT) A and on the Inhibition scale, the Behavior Regulation Index and the Global Executive Composite of the Behavioral Rating Inventory of Executive Function (BRIEF-PR). The ADHD group improved significantly on the TMT B Test, the Spatial Span Test and the Reading Fluency Test of the Woodcock-Johnson III, as well as on depressive symptoms. Our results suggest that WM training may improve WM function and support near- and far transfer, in pediatric patients with PBD or ADHD, although in different ways for the two patient groups. Future studies examining the mechanisms of cognitive remediation in pediatric patients will aid tailoring illness-specific cognitive intervention.